Factors Related To Maternal Behavior In Exclusive Breastfeeding At The Tiga Panah Health Center, Karo Regency In 2023 - Br Tarigan, Helpina; Damanik, Lisa Putri Utami; Br. Ginting, Nurleni; br Pinem, Srilina (COVID-19 : Journal of Health, Medical Records and Pharmacy, 2023)
Breast milk is the ideal nutrition for babies which contains nutrients that best suit the baby's needs and contains a set of protective substances to fight disease. The first two years of a child's life are critical, as optimal nutrition during this period decreases morbidity and mortality, reduces the risk of chronic disease, and promotes better overall development. Therefore, optimal breastfeeding, namely when children are 0-23 months old, is very important because it can save the lives of more than 820,000 children under 5 years of age every year. The percentage of exclusive breastfeeding for babies aged 0-6 months is 71.58% in 2021. This type of research is quantitative with a cross sectional approach. The research was conducted in the working area of ​​the Tiga Panah Community Health Center, Karo Regency, carried out in early 2023. The research population was all mothers who had babies aged 0-6 months in the working area of ​​the Tiga Panah Community Health Center totaling 50 people. The sampling technique used was purposive sampling. The data analysis used was univariate analysis and bivariate analysis, the analysis used was the Chi Square (X2) statistical test with α = 0.05. The results showed that 14 respondents (33.4%) were aged 20-35 years. Based on high school education, 21 respondents (50%). and most respondents did not work as many as 25 respondents (59.5%). The behavior of mothers who did not breastfeed exclusively was 9 responses (21.5%), almost half of the respondents had insufficient knowledge about breastfeeding, 14 respondents (33.4%). It was still found that (14.3%) pregnant women had readiness in the not ready category in terms of the efforts made to support successful breastfeeding efforts during pregnancy. The results of the Chi Square test with continuity correction obtained a P value of 0.003 (<0.05), meaning that there is a relationship between support from health workers and exclusive breastfeeding behavior at the Tiga Panah Community Health Center, Karo Regency. The results of statistical tests can be concluded that there is an influence of support from health workers on the behavior of exclusive breastfeeding at the Tiga Panah Community Health Center, Karo Regency with a Chi Square value by looking at the continuity correction, a P value of 0.003 (<0.05). It is hoped that health workers will provide education and communication to increase understanding of exclusive breastfeeding.